Signifikansi Pembinaan Ideologi Pancasila dalam Pendidikan Keluarga - Juwono, Hendro; Irawan, Vaesol Wahyu Eka; Rahman, Fawait Syaiful (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2022)
Family is a term for the relationship between husband and wife or parents and children. In Islam, family is a translation from Ahlun Arabic. Although the word Ahlun itself has many meanings, including groups, groups, or followers. The function of the family in the education and development of the basic values of a teaching has proven effective. The research method used is qualitative with the type of literature research. Data sources use Documentation, and Data analysis uses descriptive. Based on the results of the study, the following conclusions were obtained, pancasila Idiology is the views and principles of every citizen in the nation and state. A good citizen should reflect the paradigm, attitude, and love behavior of the Republic of Indonesia. Pancasila idiology is not just a slogan, but it animates all the activities of everyone in the territorial area of the Indonesian State. The development of Pancasila idiology based on Family education means teaching and instilling the basic principles of Pancasila through the introduction and actualization of Pancasila values into the life of the nation and state. A family consisting of husband and wife or parents and children, of course, parents are responsible for the basic education of the family. The strategic position of the family in constructing thoughts and beliefs is the main medium in the cultivation of Pancasila idiology